ORGANIZATIONAL AND METHODOLOGICAL BASES OF CHILDREN’S SPEECH DEVELOPMENT (The Conference Hub, 2025)
The functions of preschool children’s speech are multifaceted. In this case, the child uses speech to communicate with others, to draw attention to himself, his work and experiences, to understand each other, to influence the behavior, thoughts and feelings of his partner, to establish his own activities, to coordinate the actions of himself and his friends who are playing with him.This article focuses on the development of the speech of children of preschool age, their adherence to the norms of literary language, their ability to express their thoughts, feelings, and imagination in a meaningful, grammatically correct, clear and expressive manner in accordance with the direction and purpose of the speech.